2018
DOI: 10.15761/jmt.1000120
|View full text |Cite
|
Sign up to set email alerts
|

MRI detection of the activated region in the rat brain by Hochuekki-to, a traditional oriental medicine, and the related expression of BNIP-3 mRNA, a candidate of depression-related factor

Abstract: Japanese-Chinese traditional medicine (Wakan-yaku) contains various treatment prescriptions for the depression based on the peculiar theory, "mood, blood and water theory", "five elements theory" and others. I am studying to find treatment targets and therapeutic drugs of the depression by using the Wakan-yaku, mainly Hochuekki-to (HET). We have been reported that HET-and typical antidepressants-treatment enhance BINP-3 mRNA expression in cultured neuronal cell line, suggesting that BNIP-3 mRNA expression may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As described in the Introduction, we previously demonstrated that HET as well as an antidepressant treatment increased the expression levels of BNIP‐3 in NG108‐15 cells [1,2]. Previous studies also examined the function of BNIP‐3 [3,4,15]. The findings obtained are shown in Table 1, and 10 crude drugs comprising HET are shown with ‘#’ in the HET column.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As described in the Introduction, we previously demonstrated that HET as well as an antidepressant treatment increased the expression levels of BNIP‐3 in NG108‐15 cells [1,2]. Previous studies also examined the function of BNIP‐3 [3,4,15]. The findings obtained are shown in Table 1, and 10 crude drugs comprising HET are shown with ‘#’ in the HET column.…”
Section: Discussionmentioning
confidence: 86%
“…We previously reported the significant upregulation of BNIP‐3 mRNA expression when Hochuekkito (Bu Zhong Yi Qi Tang) [1], as well as many antidepressants [1,2], were added to a culture medium of NG108‐15 cells, which is a hybrid cell of neuroblastoma N18TG‐2 and glioma cell C6Bu‐1. Starting from those results, we also found that BNIP‐3 mRNA expression was also detected in brain regions with highly active nerves [3] and contributed to synaptic enhancement [4], suggesting the functional significance of BNIP‐3 in the brain. As in the case of BNIP‐3 described above, studying the effects of crude drugs and Kampo prescriptions on cultured cell lines makes it possible to obtain new findings on effects triggered by them.…”
Section: Introductionmentioning
confidence: 84%
“…Based on these facts, BNIP‐3 is considered to be a candidate as a factor in the brain related to the antidepressant effect. Studies have been conducted by us on changes in the expression during neuronal growth [4] and on analysis of the site of expression in the brain [5].…”
Section: Introductionmentioning
confidence: 99%